THE CONTENT OF THE COMPONENTS OF THE INTERNAL PATTERN OF DISORDER IN PRESCHOOL CHILDREN WITH SENSORY DISORDERS - Adeeva, T. N.; Sevastyanova, U. Yu (Modern Psychology, 2019)
The internal pattern of disorder (IPD) is considered as the structure of the Selfconcept. Features of the internal pattern of the disorder can determine the adaptation option. Self-concept of preschoolers with deficit development is characterized mainly by a high level of self-acceptance. Children with cerebral palsy have no idea of themselves as a friend due to the small number of social contacts. The content of IPD components depends on the variant of dysontogenesis and age. In contrast to younger students, the components of IPD in preschool children with speech and visual impairment are filled with little content, the cognitive component is characterized by stereotype, and sensitive, emotional motivational components do not have specifics associated with the structure of the defect. In preschool children with visual impairment noted the dominance of the emotional component in the structure of IPD. The influence of the structure of the disorder on the physical, emotional and motivational components was noted in preschool children with cerebral palsy.
Keywords: internal pattern of disorder, sensory disorders, preschool age.